Basic statistics for business & economics - Lind, Douglas A.; Marchal, William G.; Wathen, Samuel Adam. (Boston McGraw-Hill/Irwin, 2011)
What is statistics; Describing data: frequency tables, frequency distributions, and graphic presentation; Describing data: numerical measures; Describing data: displaying and exploring data; A survey of probability distributions...
Includes index.
Keywords: Social sciences -- Statistical methods; Economics -- Statistical methods; Industrial management -- Statistical methods; Toán học; Toán thống kê